Far-field nanoscale infrared spectroscopy of vibrational fingerprints of molecules with graphene plasmons - Hai Hu (Nature Portfolio, 2016)
Despite being a powerful tool for molecular vibrational mode detection, infrared spectrosocpy is limited by weak sensitivity. Here, the authors demonstrate a platform for enhanced molecular fingerprint sensing based on a graphene/CaF2nanofilm plasmonic structure.